The intersections between infrastructures and expectations: repair and breakdown in Yachay, the city of knowledge in Ecuador - José David Gómez-Urrego (Tapuya, 2019)
This paper explores the temporalities of infrastructuring, breakdown, and repair/disrepair interacting generatively – materially and symbolically – in “Yachay, the city of knowledge,” the most ambitious and controversial public infrastructural project in Ecuador’s history. I analyze the roles of expectations, and the infrastructural dynamics in the process of shaping Yachay during its intragovernmental scaling-up from a technical university to a city of knowledge; and during the material implementation of some of its basic physical infrastructure. I also highlight the embeddedness of the expectations in particular pasts and historical trajectories, thus extending the common use of expectations as only oriented to the future. The argument presented here draws on fieldwork conducted in Yachay for 14 months between 2016 and 2018.